Exchange Transfusion and Leukapheresis in Pediatric Patients with AML With High Risk of Early Death by Bleeding and Leukostasis - Creutzig, Ursula; Rössig, Claudia; Dworzak, Michael; Stary, Jan; von Stackelberg, Arend; Wössmann, Wilhelm; Zimmermann, Martin; Reinhardt, Dirk (Pediatric blood & cancer, 2016)
BACKGROUND: The risk of early death (ED) by bleeding/leukostasis is high in patients with AML with hyperleukocytosis (>100,000/μl). Within the pediatric AML-BFM (Berlin-Frankfurt-Münster) 98/04 studies, emergency strategies for these children included exchange transfusion (ET) or leukapheresis (LPh). Risk factors for ED and interventions performed were analyzed. PATIENTS: Two hundred thirty-eight of 1,251 (19%) patients with AML presented with hyperleukocytosis; 23 of 1,251 (1.8%) patients died of bleeding/leukostasis. RESULTS: ED due to bleeding/leukostasis was highest at white blood cell (WBC) count >200,000/μl (14.3%). ED rates were even higher (20%) in patients with FAB (French-American-British) M4/M5 and hyperleukocytosis >200,000/μl. Patients with WBC >200,000/μl did slightly better with ET/LPh compared to those without ET/LPh (ED rate 7.5% vs. 21.2%, P = 0.055). Multivariate WBC >200,000/μl was of strongest prognostic significance for ED (P(χ(2) ) <0.0001). CONCLUSION: Our data confirm the high risk of bleeding/leukostasis in patients with hyperleukocytosis. ET/LPh shows a trend toward reduced ED rate due to bleeding/leukostasis and is recommended at WBC >200,000/μl, and in FAB M4/M5 even at lower WBC.
Keywords: Female; Infant; Leukostasis; dítě; předškolní dítě; Blood Transfusion; krevní transfuze; ženské pohlaví; krvácení; lidé; Risk Factors; proporcionální rizikové modely; Male; kojenec; Child, Preschool; akutní myeloidní leukemie; Hemorrhage; rizikové faktory; leukostáza; Child; Leukapheresis; mužské pohlaví; leukaferéza; Proportional Hazards Models; Leukemia, Myeloid, Acute; Humans